Multivariate characterization of "Argentinean Misletoe", Ligaria cuneifolia (Loranthaceae) according to their mineral nutrient composition - Giménez, María Cecilia (2012)
The aim of this study was to characterize samples of Ligaria cuneifolia collected from three areas of the north-east region of Argentina, during two sampling periods. In this work, the authors propose a mathematical model for searching associations among mineral contents and other factors such us geographic origin or sampling period. Mineral monitoring as a pattern recognition method is a promising tool in the characterization and/or standardization of phytomedicines. In the present work measurable amounts of Al, Ca, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Na, P, Sr, and Zn were detected in phytopharmaceutical derivatives of L. cuneifolia by inductively coupled plasma optical emission spectrometry (ICP-OES). Finally, this methodology allows reliable determinations of mineral content in pharmaceutical quality control of medicinal plants.